Analisis Parameter Proses Injeksi 3D Printed VeroWhite Plus Rapid Tooling Dengan Metode Design of Experiments - Riona Ihsan Media; Ismet P. Ilyas; Mohammad Qomarudin (Rekayasa Mesin, 2022)
The insert cavity and core produced by the previous research were made using the polymer rapid tools (PRT) technique and will be used for the experimental production process. PRT is a technique for making tools with polymer materials using Additive Manufacturing (AM) technology. In this research, the polymer material used is VeroWhite Plus. The insert cavity and core will be tested to produce ± 100 key chain products. The adjustment of the injection process parameters is sought through the simulation process to obtain low insert cavity and core temperature values so that the mold is not damaged at the beginning of the injection process. There are 5 parameters of the injection process that affect the optimal mold durability, namely: mold temperature, injection speed, injection pressure, hold pressure and cooling time. The analysis was carried out using the design of experiments (DOE) method to obtain the optimal combination of injection process parameters. Analysis of the DOE method based on software simulation obtained the optimal combination of injection process parameters with details (injection speed: 5 mm / s, injection pressure: 15 Mpa, holding pressure: 10 Mpa and cooling time: 100 seconds). The durability of the insert cavity and core produced by PRT is able to produce products as desired by 100 products or even more.